Recent trends in sustainable modelling for hydrogen production and utilization - April Lia Hananto; Abdullahi Tanko Mohammed; Permana Andi Paristiawan; Ihwan Ghazali; Muhammad Idris; Syah Alam; Mega Tri Kurnia (Jurnal POLIMESIN, 2023)
Hydrogen is a promising candidate for the future of energy and global economic security owing to its cost-efficient clean and environmentally friendly nature. The utilisation of hydrogen is, however, not without obstacles. Technology maturity and the unattractive market are some of the challenges. Before hydrogen can be used on a large-scale basis, critical technical challenges need to be addressed, such as the economical production and transportation and storage issues. In terms of energy prices, hydrogen is an inexpensive fuel. Ideally, a vehicle run on hydrogen reduces the cost per kilometre with better mileage than that of fuelled with fossil fuel. Electric vehicles run on hydrogen fuel cells, for instance, offer several performance improvements over conventional internal combustion engines. This includes better fuel efficiency and relatively less noise operation, yet one of the important technical challenges is onboard hydrogen storage. In this review article, recent trends in modeling for hydrogen production and utilization are addressed in detail.